2000
DOI: 10.1097/00000542-200004000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Uncertainty of Surgical Procedure Times

Abstract: The authors recommend use of the log-normal model for predicting surgical procedure times for Current Procedural Terminology-anesthesia combinations. The results help to legitimize the use of log transforms to normalize surgical procedure times before hypothesis testing using linear statistical models or other parametric statistical tests to investigate factors affecting the duration of surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(101 citation statements)
references
References 2 publications
3
96
0
2
Order By: Relevance
“…Data had been approved immediately after the surgical procedure by the surgery or anaesthesia nurse. The duration of surgical procedures, both emergency and elective, is assumed to be lognormal [3]. Table 1 shows the aggregate descriptive statistics of the central OR department of the Erasmus MC.…”
Section: Methodsmentioning
confidence: 99%
“…Data had been approved immediately after the surgical procedure by the surgery or anaesthesia nurse. The duration of surgical procedures, both emergency and elective, is assumed to be lognormal [3]. Table 1 shows the aggregate descriptive statistics of the central OR department of the Erasmus MC.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in [30] it was shown that lognormal distributions model the uncertainty of surgical procedure times better than normal distributions. A consequent line of research explores different methods for fitting lognormal distributions, e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pre-surgery set-up time and post-surgery operating room cleaning time, if significant, is also added to the model (see Spangler et al [2004], Strum et al [2000], and May et al [2000]). …”
Section: Simulation Modelingmentioning
confidence: 99%